Critical Factors to Technology Development in Indian Academia : An ISM-MICMAC Approach - Kanojia, Meenakshi; Shukla, Balvinder; Wali, Anil (Prabandhan: Indian Journal of Management, 2022)
The significance of research translation and technology transfer in academia is getting increasing attention for the greater public interest. Besides, the successful transfer of knowledge to augment a university’s outreach mission is in a large measure driven by R&D outcomes, more particularly, in terms of developed technologies. It thus becomes worthwhile to analyze the factors that enable technology development in academia. This objective remains a gap in extant literature. Therefore, this study aimed to identify the enabling factors of technology development in the university ecosystem and to examine their interrelationships. An interpretive structural modelling (ISM) technique was applied to identify the interrelationship among factors. Further, MICMAC analysis was applied to identify the driving and dependent enabling factors. Our findings revealed that top management’s leadership and visionary approach ; research mission ; strategy & culture ; adequate research infrastructure ; and intramural funding for research, development, and innovation-related activities are the key driving factors to technology development in academia. This study will be useful for the managers and decision-makers to comprehend the relationship between technology development enablers and framing the institutional policies and strategies.